Combinatorial Investigation of the Ni–Ta System via Correlated High‐Speed Nanoindentation and EDX Mapping. Issue 2 (28th November 2021) - Wheeler, Jeffrey M.; Gan, Bin; Spolenak, Ralph
Abstract: Correlated high‐speed nanoindentation and energy‐dispersive spectroscopy are applied in a combinatorial investigation of the Ni–Ta system. All seven phases in the system are clearly resolved in the resulting maps, and the mechanical properties and composition ranges for each phase are determined. Good agreement with ab initio calculations is generally observed with some exceptions, most notably NiTa2 . This is achieved using a simple correlation method utilizing directly overlaid data matrices to allow compositional labeling of mechanical data. This allows easy data segmentation without requiring complicated statistical deconvolution methods. Without this correlative method, phase deconvolution of the Ni–Ta system would be challenging due to several phases possessing adjacent compositions and mechanical properties. This demonstrates the potential of this new correlative approach for future investigations, particularly those involving complex microstructures and/or compositional variation. Abstract : A direct, combinatorial method for correlating compositional and mechanical datasets from high‐speed nanoindentation and energy‐dispersive X‐ray spectroscopy mapping, allowing the extraction of phase‐level data and trends in mechanical properties, is demonstrated on a Ni–Ta diffusion couple. This method yields paired compositional and mechanical data of an entire microstructural cross‐section, independent of the spatial distribution and morphology of the phases.